ACTIVE FORMS OF CAREER GUIDANCE WORK IN SCHOOL (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This paper examines active forms of career guidance activities in comprehensive schools as an important means of preparing students for an informed choice of their future profession. The importance of integrating such forms into the educational process, as well as the role of teachers, psychologists and social partners in organizing effective career guidance work, is noted.